Retinal haemorrhage description tool. Issue 12 (8th October 2011) - Tandon, Anamika; McIntyre, Susan; Yu, Anna; Stephens, Derek; Leiby, Benjamin; Croker, Sean; Levin, Alex V
Abstract : Background: Retinal haemorrhages are an important finding in children with abusive and accidental head trauma. There are no standardised and validated protocols to describe them in a consistent manner. The aim of this web-based study was to establish the reliability and validity of a new retinal haemorrhage description tool. Materials and method: Our tool is a comprehensive questionnaire, which is applied using a retinal schematic that divides the retina into four independent zones. Four independent observers scored retinal haemorrhages from 80 retinal photographs. Inter- and intra-rater agreement (by repeat assessment of 10 photographs for each examiner) were calculated using Fleiss κ statistics. Results: A high inter-rater agreement was noted for haemorrhages in the peripapillary zones, whereas agreement was only fair for all other zones. Intra-rater agreement was high only for the posterior pole. Photographs may be an unreliable way of documenting retinal haemorrhages particularly from the peripheral retina, thus underscoring the importance of a thorough clinical examination. Conclusion: This study shows that the tool achieves some validity for describing haemorrhages in the posterior retina. It performs less well in the peripheral zones.